Greenland's project independence: Ambitions and prospects after 300 Years with the Kingdom of Denmark - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2021)
An important anniversary is coming up in the Kingdom of Denmark: 12 May 2021 marks exactly three hundred years since the Protestant preacher Hans Egede set sail, with the blessing of the Danish monarch, to missionise the island of Greenland. For some Greenlanders that date symbolises the end of their autonomy: not a date to celebrate but an occasion to declare independence from Denmark, after becoming an autonomous territory in 2009. Just as controversial as Egede's statue in the capital Nuuk was US President Donald Trump's offer to purchase the island from Denmark. His arrogance angered Greenlanders, but also unsettled them by exposing the shaky foundations of their independence ambitions. In the absence of governmental and economic preconditions, leaving the Realm of the Danish Crown would appear to be a decidedly long-term option. But an ambitious new prime minister in Nuuk could boost the independence process in 2021.
Keywords: 320